On Some Extremal Problems on Linearly Invariant Classes - Kiriyatzkii, E. G.; Kirjackis, J. (Nonlinear Analysis: Modelling and Control, 2005)
In present paper the definition of linearly invariant class of analytical in the right half-plane is given and some extremal problems on introduced class are solved. For solving we use method based on variational formulas with specially introduced omega-operator, defined on these classes. In case when domain is unit disk similar linearly invariant classes were considered by Ch. Pommerenke, V. Starkov, E.G. Kiriyatzkii.